2020
DOI: 10.3390/diagnostics10050260
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gene Polymorphisms in GAS5 on Urothelial Cell Carcinoma Development and Clinical Characteristics

Abstract: Urothelial cell carcinoma (UCC) is the commonest malignant tumor of the urinary tract and the second most common kidney cancer malignancy. Growth arrest-specific 5 (GAS5), a long noncoding RNA, is encoded by the GAS5 gene and plays a critical role in cellular growth arrest and apoptosis. In the current study, two single nucleotide polymorphisms (SNPs) in the GAS5 gene, rs145204276 and rs55829688, were selected to investigate correlations between these single SNPs and susceptibility to UCC. A total of 430 UCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The growth arrest-specific 5 (GAS5) is a type of long non-coding RNA that acts as a tumor suppressor and influences the cell apoptosis and tumorigenesis processes in accordance with previous publications [ 12 , 13 , 14 ]. Regarding the SNP of GAS5 , the GAS5 SNP rs145204276 increases the probability of larger tumor status in urothelial cell carcinoma [ 13 ]. In addition, the GAS5 SNP rs145204276 is significantly correlated with lung cancer susceptibility [ 15 ].…”
Section: Introductionsupporting
confidence: 83%
“…The growth arrest-specific 5 (GAS5) is a type of long non-coding RNA that acts as a tumor suppressor and influences the cell apoptosis and tumorigenesis processes in accordance with previous publications [ 12 , 13 , 14 ]. Regarding the SNP of GAS5 , the GAS5 SNP rs145204276 increases the probability of larger tumor status in urothelial cell carcinoma [ 13 ]. In addition, the GAS5 SNP rs145204276 is significantly correlated with lung cancer susceptibility [ 15 ].…”
Section: Introductionsupporting
confidence: 83%
“…SNPs of lncRNAs have been proposed to influence certain types of malignancies and angiogenic diseases ( Peng et al, 2017 ; Yuan et al, 2019 ; Weng et al, 2020 ; Ding et al, 2021 ; Wang et al, 2021 ). In previous studies, lncRNA CCAT1 SNP rs67085638 was correlated with the development of gastric cancer ( Olesiński et al, 2021 ), and lncRNA PCAT1 and its SNP rs2632159 were associated with a higher rate of colon cancer, which involves an angiogenesis process ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for the factor that controls cell growth, the MIR4435-2HG caused the up-regulation of TGF-β1 in oral squamous cell carcinoma [ 39 ]. Regarding the aspect of GAS5, it was proven to alter the tumor expression in several types of neoplasms [ 22 , 28 ]. Although the majority of malignancies were suppressed via the higher level of GAS5 [ 21 , 23 , 27 ], certain cancers benefited from the presence of GAS5 [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two SNPs of GAS5 , meaning the rs145204276 (Ins/Del) and the rs55829688 (T/C), were chosen since their minor allele frequencies were more than 5 percent, and earlier studies indicated their influence in other cancers [ 26 , 27 ]. The genotyping procedure used in the current study was similar as a previous study [ 28 ]; the genome was firstly extracted from the leukocytes in the venous blood from each participant via the QIAamp DNA kits (Qiagen, Valencia, Valencia, CA, USA) according to the manufacturer’s instruction for DNA isolation [ 29 , 30 ]. Then, the isolated DNA was stored at –20 degrees Celsius.…”
Section: Methodsmentioning
confidence: 99%